Techno-Economic Study of a New Hybrid Solar Desalination System for Producing Fresh Water in a Hot–Arid Climate - Mahmoud Makkiabadi (MDPI AG, 2021)
By taking advantage of the obtained experimental data, the impact of employing concentrating solar collectors, using an electric heater, and changing the water height in the basin on the performance of a hybrid solar still system was investigated. Eight different operating modes for the system were studied, while the daily freshwater production in addition to the cost per liter (CPL) was considered as the performance criteria. According to the results, the best height of water in the basin is 10 mm. It is the lowest examined height. Moreover, it was found that using the hybrid system with both electric heater and concentrating solar heater brings considerable improvements compared to the other investigated operating modes. For the climatic condition of Sirjan, Iran, which is where the experiments were performed, and water height in the basin of 10 mm, using the hybrid system in the active mode results in 8178 mL/m2 of fresh water production, and a CPL of $0.04270 per liter.